2010
DOI: 10.1063/1.3284088
|View full text |Cite
|
Sign up to set email alerts
|

Thermal expansion of skutterudites

Abstract: The current paper gives an overview of the newly obtained thermal expansion coefficients of skutterudites as well as those so far available in literature. Thermal expansion was determined for CoSb 3 , Pt 4 Sn 4.4 Sb 7.6 , for As-and Ge-based skutterudites as well as for various high-ZT skutterudites ͑microand nanostructured͒ with didymium ͑DD͒ and mischmetal ͑Mm͒ as filler atoms in frameworks of ͑Fe 1−x Co x ͒ 4 Sb 12 and ͑Fe 1−x Ni x ͒ 4 Sb 12 , and for double and triple-filled skutterudites such as Ca 0.07 B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 35 publications
4
47
0
Order By: Relevance
“…20a and b) with a ¼ 11.85 Â 10 À6 K À1 and a ¼ 11.86 Â 10 À6 K À1 respectively can be considered equal; this is not surprising since a previous investigation demonstrated that skutterudites with similar compositions and filling levels have thermal expansion coefficients in the same range (see Table 2). The values compare well with those of DD 0.44 Fe 2.1 Co 1.9 Sb 12 or Mm 0.70 Fe 3 CoSb 12 [50].…”
Section: Thermal Expansion and Mechanical Propertiessupporting
confidence: 69%
See 3 more Smart Citations
“…20a and b) with a ¼ 11.85 Â 10 À6 K À1 and a ¼ 11.86 Â 10 À6 K À1 respectively can be considered equal; this is not surprising since a previous investigation demonstrated that skutterudites with similar compositions and filling levels have thermal expansion coefficients in the same range (see Table 2). The values compare well with those of DD 0.44 Fe 2.1 Co 1.9 Sb 12 or Mm 0.70 Fe 3 CoSb 12 [50].…”
Section: Thermal Expansion and Mechanical Propertiessupporting
confidence: 69%
“…Thermal expansion was measured at low (4.2e300 K) and high temperature (300e800 K) as described in Ref. [50]. Young's modulus E Y and Poisson's ratio n were measured via resonant ultrasound spectroscopy, bulk modulus B and shear modulus G were calculated with the data of E Y and n. For DD 0.65 Fe 3 CoSb 12 Young's modulus was also measured in the temperature range of 300e700 K in steps of DT ¼ 100K.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The improved performance of some multiply filled skutterudites 8,[36][37][38][39][40][41][42][43][44][45][46] may be explained in part from nanodomains with avoided crossings at different qvectors. However, in many cases the concentrations of some filler atom are low and in that case defect scattering should also play an important role.…”
Section: Discussionmentioning
confidence: 99%